Regulatory Effects of Zhenxin Formula in Treating Doxorubicin-Induced Heart Failure: Network Pharmacology and Animal Experimental Verification - Wu Q; Wang H; Wang YH; Du J; Li B; Gan XN; Liu CY; Liang J; Liu C; Cao M (Drug Design, Development and Therapy, 2025)
Qiong Wu,1,* Hao Wang,2,* You Hua Wang,1 Jun Du,3 Bo Li,3 Xiao-Na Gan,3 Chen-Yang Liu,2 Jing Liang,2 Chang Liu,2 Min Cao2 1Department of Cardiology, Longhua Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 2Department of Emergency, Longhua Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 3Nutrilite Health Institute, Amway (China) R&D Center, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chang Liu, Department of Emergency, Longhua Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, Xunhui, 725 South Wan-Ping Road, Shanghai, 200032, People’s Republic of China, Tel +862164385700, Email doctorlchang@163.com Min Cao, Department of Emergency, Longhua Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, Xunhui, 725 South Wan-Ping Road, Shanghai, 200032, People’s Republic of China, Tel +862164385700, Email caomin_cm@163.comObjective: This study aimed to elucidate the mechanisms underlying the protective effects of Zhenxin Formula (ZXF) against doxorubicin (Dox)-induced HF through the integration of network pharmacology, phospho-antibody array analysis, and experimental validation.Methods: The active components and potential targets of ZXF were identified via the Traditional Chinese Medicine Systems Pharmacology (TCMSP) platform, while HF-associated target genes were retrieved from the OMIM, Genecards, and TTD databases. Protein-protein interaction (PPI) networks and compound-disease target networks were constructed using Cytoscape 3.7.2, with functional annotations performed through GO enrichment and KEGG pathway analyses using R software. Experimental validation involved the establishment of a Dox-induced HF model via intraperitoneal injection, with ZXF’s therapeutic effects evaluated using cardiac ultrasound, morphological staining, and Western blot analysis. Additionally, a phospho-antibody array was utilized to screen over 300 molecules across 16 canonical signaling pathways in ZXF-treated HF models, with Western blot analysis confirming the specific pathways implicated in ZXF’s therapeutic effects.Results: Network pharmacology analysis identified 56 potential active ingredients in ZXF, 47 of which were associated with HF-related targets. AKT1 emerged as the target most strongly correlated with HF improvement. In vivo, ZXF significantly enhanced cardiac function and mitigated myocardial fibrosis and cardiomyocyte apoptosis. Phospho-antibody array analysis revealed that 16 phosphorylated proteins were upregulated and 3 downregulated in the Dox-treated group. ZXF intervention resulted in the upregulation of 10 phosphorylated proteins and downregulation of 5. Comparative analysis highlighted PDK1-Phospho and FOXO1/3/4-Phospho as pivotal phosphorylated proteins mediating ZXF’s cardioprotective effects. Western blot analysis confirmed that ZXF enhanced phosphorylation levels of PI3K, PDK1, AKT, and FOXO1 in the Dox-induced HF model.Conclusion: This study, employing network pharmacology, phospho-antibody array analysis, and experimental validation, demonstrates that ZXF ameliorates cardiac dysfunction and suppresses myocardial apoptosis in Dox-induced HF through modulation of the PI3K/PDK1/AKT/FOXO1 signaling pathway.Keywords: network pharmacology, phospho-antibody array, Zhenxin Formula, heart failure, PI3K/PDK1/AKT/FOXO1 signaling pathway